Resveratrol inhibits phorbol ester-induced membrane translocation of presynaptic Munc13-1 - Pany, Satyabrata; Ghosh, Anamitra; You, Youngki; Nguyen, Nga; Das, Joydip (Biochimica et biophysica acta, 2017)
Resveratrol (1) is a naturally occurring polyphenol that has been implicated in neuroprotection. One of resveratrol's several biological targets is Ca2+-sensitive protein kinase C alpha (PKCα). Resveratrol inhibits PKCα by binding to its activator-binding C1 domain. Munc13-1 is a C1 domain-containing Ca2+-sensitive SNARE complex protein essential for vesicle priming and neurotransmitter release. To test if resveratrol could also bind and inhibit Munc13-1, we studied the interaction of resveratrol and its derivatives, (E)-1,3-dimethoxy-5-(4-methoxystyryl)benzene, (E)-5,5′-(ethene-1,2-diyl)bis(benzene-1,2,3-triol), (E)-1,2-bis(3,4,5-trimethoxyphenyl)ethane, and (E)-5-(4-(hexadecyloxy)-3,5-dihydroxystyryl)benzene-1,2,3-triol with Munc13-1 by studying its membrane translocation from cytosol to plasma membrane in HT22 cells and primary hippocampal neurons. Resveratrol, but not the derivatives inhibited phorbol ester-induced Munc13-1 translocation from cytosol to membrane in HT22 cells and primary hippocampal neurons, as evidenced by immunoblot analysis and confocal microscopy. Resveratrol did not show any effect on Munc13-1H567K, a mutant which is not sensitive to phorbol ester. Binding studies with Munc13-1 C1 indicated that resveratrol competes with phorbol ester for the binding site. Molecular docking and dynamics studies suggested that hydroxyl groups of resveratrol interact with phorbol-ester binding residues in the binding pocket. This study characterizes Munc13-1 as a target of resveratrol and highlights the importance of dietary polyphenol in the management of neurodegenerative diseases. [Display omitted] •Resveratrol binds to the C1 domain of SNARE complex protein Munc13-1•Resveratrol inhibits the activity of Munc13-1 in HT-22 cells and primary hippocampal neurons.•Dietary polyphenols are important in the management of neurodegenerative diseases.